Analisis Pengaruh Gaya Kepemimpinan Dan Disiplin Kerja Terhadap Efektivitas Kerja Guru di SMK Hidayatul Islam Clarak Kecamatan Leces Kabupaten Probolinggo - Moh. Saiful Bahri (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2016)
This study was conducted aiming to determine the effect of Style Leadership and Effectiveness Against Work Discipline Teachers Working in SMK Islam Hidayatul Clarak Leces District of Probolinggo. The population in this study was a teacher in SMK Islam Hidayatul Clarak Leces District of Probolinggo, amounting to 18 people. The sample used in this study is the entire population. The independent variables namely Leadership Style (X1) and discipline (X2), while the dependent variable is the effectiveness of the work (Y). While the data collection methods used are questionnaires. This type of research is associative research. The results were obtained 1) The equation Y = 8.337 + 0,559X1 + 0,147X2 on multiple linear re- gression analysis, this means the Leadership Style (X1) and discipline (X2) have an influence on the effec- tiveness of (Y). 2) The calculation coefficient of determination (R Square) of 0.385. This suggests that the effect of variable X (Style of Leadership and discipline) to variation (up and down) variable Y (the effec- tiveness of) by 38.5%, while the remaining 61.5% came from other factors apart from Leadership Style and work discipline. 3) F test results showed a value of 4.689 with a significance level of 0.026. Thus Fhitung = 4.689> F table = 3.682, then H0 rejected and Ha accepted. This indicates that the variable leadership style and work discipline has a positive and significant effect simultaneously on the effectiveness of the work of teachers in vocational Hidayatul Islam Clarak District of Leces Probolinggo. 4) Value thitung X1 = 2,952> t table = 2.131, then H0 rejected and Ha accepted, meaning that no partial significant influence among the leadership style of the effectiveness of the work. Tcount X2 = 0,829 <table = 2.131, then H0 rejected and Ha accepted, meaning that no partial significant influence between work discipline on the effectiveness of the work. 5) Value thitung X1 = 2,952> Value thitung X2 = 0.829, meaning that leadership style variable (X1) has dominant influence (most) of the effectiveness of the work (Y) in SMK Islam Hidayatul Clarak Leces District of Probolinggo.